2020
DOI: 10.3390/app10031003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soccer Training on Body Balance in Young Female Athletes Assessed Using Computerized Dynamic Posturography

Abstract: The aim of this study was to determine the effect of regular soccer training on the balance system for young women. Computerized dynamic posturography of female footballers (n = 25) and control group (n = 50) was assessed during three tests: Sensory Organization Test, Motor Control Test, and Adaptation Test. Statistically significant differences between the groups was found in Composite Equilibrium Score with higher values, indicating better postural stability, for footballers. Regular trainees also showed bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The problem of the influence of regular football training on balance was investigated by Olchowiak G. and Czwalik A. [ 25 ]. The authors carried out research on women training in football ( n = 25) and a control group ( n = 50).…”
Section: Discussionmentioning
confidence: 99%
“…The problem of the influence of regular football training on balance was investigated by Olchowiak G. and Czwalik A. [ 25 ]. The authors carried out research on women training in football ( n = 25) and a control group ( n = 50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SOT performance can be influenced by an individual's balance training (e.g., highly trained world-class athletes, 48 circus performers, 49 or military personnel 50 ) and might differ from SOT performance in the general population. 49 Children who are frequently involved in sports have better muscle strength and postural control.…”
Section: Physical Activities and Sports Effectmentioning
confidence: 99%
“…For example, the NeuroCom SMART Balance Master can score a user’s performance through the sensory organization test of equilibrium and motor control test ( Wagner et al, 2016 ). The sensory organization test evaluates postural stability under various sensory conditions, where the visual, proprioceptive, and vestibular senses are altered ( Wagner et al, 2016 ; Olchowik and Czwalik, 2020 ). A final “equilibrium score” based on the center of gravity sway is associated to the sensory organization test to evaluate postural stability.…”
Section: Introductionmentioning
confidence: 99%